An Effective and Feasible Method, "Hammering Technique, " for Percutaneous Fixation of Anterior Column Acetabular Fracture. (14th July 2016) - Zhang, Lihai; Yin, Peng; Zhang, Wei; Li, Tongtong; Li, Jiantao; Chen, Hua; Yao, Qi; Tang, Peifu
Abstract : Objective . The objective of this study was to evaluate the effectiveness and advantages of percutaneous fixation of anterior column acetabular fracture with "hammering technique." Materials and Methods . We retrospectively reviewed 16 patients with percutaneous fixation of anterior column acetabular fracture with "hammering technique." There were 11 males and 5 females with an average age of 38.88 years (range: 24–54 years) in our study. Our study included 7 nondisplaced fractures, 6 mild displaced fractures (<2 mm), and 5 displaced fractures (>2 mm). The mean time from injury to surgery was 4.5 days (range: 2–7 days). Results . The average of operation time was 27.56 minutes (range: 15–45 minutes), and the mean blood loss was 55.28 mL (range: 15–100 mL). The mean fluoroscopic time was 54.78 seconds (range: 40–77 seconds). The first pass of the guide wire was acceptable without cortical perforation or intra-articular perforation in 88.89% (16/18) of the procedures, and the second attempt was in 11.11% (2/18). Conclusion . Our study suggested that percutaneous fixation of anterior column acetabular fracture with "hammering technique" acquired satisfying surgical and clinical outcomes. It may be an alternative satisfying treatment for percutaneous fixation of anterior column acetabular fracture by 2D fluoroscopy using a C-arm with less fluoroscopic time.